Courage as Attack or Endurance: Debates in the Black Intellectual Tradition over How to Combat Racism - Hibbs, Thomas S. (The Thomist, 2025)
Aquinas distinguishes two senses of courage: as direct attack against evil, especially evil that threatens justice, and as a form of endurance in the face of evil that cannot easily or quickly be overcome. In the Black intellectual tradition, particularly in the writings Martin Luther King, Jr., and Malcolm X, there is sustained reflection on the role and nature of courage in response to injustice. This essay lays out Aquinas’s position and then put it in conversation with leading thinkers in the Black intellectual tradition and shows that both traditions can benefit from comparative analysis. It turns out that the significance of philosophical insights (from Aquinas) marginalized in the modern world can be highlighted by reflecting on the thought of marginalized traditions in the modern world.